CURRENT VENOUS THROMBOEMBOLISM CHEMOPROPHYLAXIS PRACTICES AFTER SURGERY FOR IBD: SAVES-IBD TRIAL INITIAL REPORT. (22nd January 2022) - Holubar, Stefan; Eisenstein, Samuel; Bordeianou, Liliana; Scow, Jeffrey; Prien, Christopher; Steinhagen, Randolph; Fichera, Alessandro; Hull, Tracy
Abstract: BACKGROUND: Despite standard of care chemoprophylaxis, postoperative VTEs occur in ∼4% of IBD patients, and little data on current practices in IBD has been reported. We cultivated a baseline cohort to inform power calculations for a forthcoming prospective, multicenter trial of VTE prophylaxis comparing the efficacy & safety of standard of care vs. aspirin (SAVES-IBD Trial). In this initial report we describe the current standard of care VTE prophylaxis practice patterns in our collaborative. METHODS: The National Surgical Quality Improvement Program (NSQIP) IBD Collaborative designed and implemented 6 VTE specific-variables including 1) Inpatient VTE chemoprophylaxis, 2) extended (post-discharge) prophylaxis, 3) length of time on primary prophylaxis, 4) VTE location, and 30-days bleeding requiring 5) transfusion or 6) reoperation. Data was collected prospectively from Sept 2020 – Mar 2021. Patients age >18 undergoing elective or emergent colectomy or proctectomy with a post-op IBD diagnosis were included. Patients with VTE present at admission (n=10, 2.3%) were excluded. RESULTS: Over 6-months, 434 patients from 13 centers were accrued; median 22 cases, IQR 18.5 – 28. Demographics: median age 41.5 years, 50% female, median BMI 24.7 kg/m 2 . Diagnoses: 263 (60.9%) Crohn's vs. 169 (39%) UC/IBDu, while 359 (82.7%) and 75 (17.3%) patients underwent colectomy and proctectomy, respectively including 69 (15.9%) IPAAs and 256 (59.0%) ileostomies, and 21 (4.8%) emergency cases. IBD Medications: 237 (54.6%) biologics, 233 (53.7%) steroids, 51 (11.8%) immunomodulators. A total of 395 (91.4%) received inpatient chemoprophylaxis including LMWH in 236 (59.7%), UFH in 158 (40.0%), DOAC in 1 (0.3%), and aspirin (none), and no chemoprophylaxis in 37 (8.5%). Extended chemoprophylaxis was utilized in 209 (48.7%) and included LMWH in 179 (85.6%), DOAC in 18 (8.6%), aspirin in 7 (3.3%), and UFH in 5 (2.4%). Overall, bleeding complications occurred in 38 (8.8%) patients with 34 (8.4%) requiring transfusion and 9 (2.1%) needing reoperation. Postoperatively, VTEs were diagnosed in 19 (4.4%) patients. VTE locations: portomesenteric vein thrombosis 8 (42%), upper extremity 3 (15.8%) or lower extremity 3 (15.8%) DVT, pulmonary embolism 2 (10.5%), and other 3 (15.8%). Univariate analysis of risk factors is shown in Table 1. Patients with 0-2 risk factors had a VTE rate of 2.9%, while in those with >2 risk factors, 31.8% developed VTE (p<0.0001). CONCLUSION: In this cohort of surgical IBD patients from IBD specialty centers, we observed a 2.3% rate of pre-operative, and a 4.4% rate of post-operative, VTE. These rates have informed the SAVES-IBD power calculations. We also observed that almost half of IBD surgery patients in these centers were prescribed extended chemoprophylaxis, most commonly with enoxaparin, rarely with aspirin. Validation of the prophylaxis variables is in-progress.